Fuel battery cell assembly
By integrating a gasket with a separator using ethylene-propylene rubber and polypropylene resin, the fuel cell assembly achieves enhanced sealing performance and durability in humid heat environments, addressing adhesive strength and moisture resistance issues.
Patent Information
- Application Number
- JP2024099963
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-23
- Filing Date
- 2024-06-20
- Publication Date
- 2025-01-09
AI Technical Summary
Existing fuel cell assemblies face challenges in maintaining high sealing performance and durability due to insufficient adhesive strength and moisture resistance of gaskets in humid heat environments, particularly in long-term operations of commercial vehicles.
The integration of a gasket with a separator using an adhesive member composed of ethylene-propylene rubber or ethylene-butene-diene rubber, combined with a polypropylene resin having a specific melt flow rate, enhances adhesiveness and moisture resistance, ensuring durable sealing performance.
The solution provides improved adhesiveness and moisture resistance, maintaining high sealing performance and durability of fuel cell assemblies even in humid heat environments, enhancing productivity and reducing oxidative deterioration.
Smart Images

Figure 2025003403000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a fuel cell assembly in which at least one of an electrode member and a separator is integrated with a gasket by an adhesive member. [Background technology]
[0002] A fuel cell has a stack structure in which many cells are stacked. The stack of cells is fastened by end plates arranged on both sides in the stacking direction. For example, a cell of a polymer electrolyte fuel cell has an electrode member having a membrane electrode assembly (MEA) and a gas diffusion layer, a separator arranged to sandwich the electrode member, and a rubber gasket arranged around the electrode member to seal the electrode member against reaction gas and refrigerant. A polymer membrane such as a fully fluorinated sulfonic acid membrane is used for the electrolyte membrane of the MEA. For this reason, when a rubber composition, which is the material of the gasket, is arranged near the MEA and cured, it is necessary to take care that the electrolyte membrane does not deteriorate due to heating during curing. In addition, even when a separator formed containing a resin is used, it is necessary to take care that the separator is deformed or deteriorated due to heating. In addition, when a rubber composition is injection molded, it is necessary to take care that the gas diffusion layer is not damaged by the injection pressure.
[0003] As the rubber component of the gasket, solid rubber such as ethylene-propylene-diene rubber (EPDM) is used from the viewpoints of durability, excellent high-temperature properties, and low gas permeability. Solid rubber is a solid that can be kneaded at room temperature, but has low fluidity compared to liquid rubber such as silicone rubber. In addition, at temperatures considering the heat resistance temperature of electrolyte membranes, etc., the curing time must be extended, resulting in reduced productivity. Therefore, when solid rubber is used, a method is adopted in which a gasket is manufactured in advance from a rubber composition and then adhered to a mating member using an adhesive, rather than a method of adhering to a mating member by utilizing the curing of the rubber composition, as in injection molding.
[0004] For example, Patent Document 1 describes a method of bonding a rubber gasket to a metal member by applying a primer to a part of the surface of the rubber gasket, bringing the primer-coated surface into close contact with the metal member constituting the fuel cell, and heating the rubber gasket in a pressure-fixed state. Examples of primers include silane coupling agent-based primers and modified olefin-based adhesives. Patent Document 2 describes that an adhesive layer that bonds a fuel cell component to a crosslinked rubber member is formed from a liquid composition containing a powder of an olefin-based thermoplastic resin modified with acid and a liquid containing a silane coupling agent. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-183198 A [Patent Document 2] JP 2023-34863 A [Patent Document 3] JP 2014-22131 A [Patent Document 4] JP 2007-66766 A Summary of the Invention [Problem to be solved by the invention]
[0006] In order to improve the sealing performance of the gasket, it is necessary to improve the adhesiveness with the mating member. When a solid polymer fuel cell is operated, the components are exposed to an environment (humid and hot environment) where moisture is present at a temperature of about 70 to 90°C. Therefore, the adhesive material that bonds the gasket to the mating member is required to have initial (before use) adhesiveness, as well as humid and hot durability that prevents the adhesive strength from decreasing even when used in a humid and hot environment. In particular, when fuel cells are installed in commercial vehicles such as buses and trucks that are required to be driven for long periods of time, the adhesive material is required to have higher humid and hot durability.
[0007] In this respect, according to the adhesion method described in Patent Document 1, the mating member is limited to a metal member, and the moist heat durability of the primer is insufficient. In addition, as described in the same document, a rubber gasket coated with a primer is pressure-bonded to a metal member and kept at a temperature of 50 to 120°C for 24 hours or more, it takes a long time to develop the adhesiveness due to the silane coupling agent, so productivity is low. In the adhesive layer described in Patent Document 2, a silane coupling agent is also essential, and although the adhesion time can be shortened by using a powder of an acid-modified olefin thermoplastic resin in combination, the moist heat durability is not sufficient.
[0008] The present disclosure has been made in consideration of the above circumstances, and has an object to provide a fuel cell assembly having excellent durability, in which components are bonded together with an adhesive member having excellent resistance to wet heat. [Means for solving the problem]
[0009] (1) In order to solve the above problems, the present disclosure provides a fuel cell assembly comprising: an electrode member having a membrane electrode assembly having an electrolyte membrane and an electrode catalyst layer; a gasket made of a rubber composition having solid rubber, arranged on the outer side of the electrode member in a plane direction intersecting a thickness direction of the electrode member; a separator laminated to the electrode member and the gasket; and an adhesive member having a polypropylene-based resin and bonding at least one of the electrode member and the separator to the gasket, wherein the solid rubber is one or more selected from ethylene-propylene rubber, ethylene-propylene-diene rubber, and ethylene-butene-diene rubber, and the polypropylene-based resin has a melt flow rate (MFR) of 7 g / 10 min or more and 700 g / 10 min or less, measured at a temperature of 230° C. under a load of 2.16 kg.
[0010] In the fuel cell assembly of the present disclosure, the gasket is bonded to either one or both of the electrode member and the separator by an adhesive member having a thermoplastic polypropylene-based resin. The MFR of the polypropylene-based resin used as the adhesive member is 7 g / 10 min or more. Unless otherwise specified, the MFR in this specification is a value measured at a temperature of 230° C. and a load of 2.16 kg. In the polypropylene-based resin, when the MFR is relatively large, such as 7 g / 10 min or more, the molecular weight is relatively small. Therefore, it is considered that the relatively low molecular weight polypropylene-based resin penetrates between the rubber molecules of the gasket to be bonded, and the intermolecular force acts, thereby improving the adhesiveness. Here, the solid rubber used as the rubber component of the gasket is selected from ethylene-propylene rubber, ethylene-propylene-diene rubber, and ethylene-butene-diene rubber. Generally, it is known that olefin resins and ethylene-propylene rubbers are difficult to adhere to each other, but in the fuel cell assembly of the present disclosure, in addition to the excellent properties required for the gasket of a fuel cell, such as the sealing property, the compatibility with the polypropylene resin is improved by selecting the above three types of rubbers that have SP values (solubility parameters) close to those of the polypropylene resin, thereby improving the adhesion. In this way, the adhesive member and the gasket are firmly adhered to each other, so that moisture and oxygen are less likely to penetrate, and oxidation deterioration of the resin is suppressed, improving the durability of the adhesive member in a humid and hot environment. As a result, the high sealing property of the gasket can be maintained even when the fuel cell is operated for a long time, and a fuel cell assembly with excellent durability can be realized.
[0011] In addition, when the MFR of the polypropylene resin is relatively large, such as 7 g / 10 min or more, the viscosity at the time of melting becomes relatively small. Therefore, for example, when the adhesive composition, which is the material of the adhesive member, is applied to the member to be bonded using a dispenser or the like, the molten adhesive composition is easily discharged, and productivity can be improved. In addition, as described later, when the electrode member has a gas diffusion layer and the adhesive member is arranged so as to contact the gas diffusion layer, the adhesive composition can be impregnated into the gas diffusion layer to improve adhesion. On the other hand, if the MFR of the polypropylene resin is too large, the molecular weight becomes too small and the melting point decreases. In this case, the adhesive member may be deformed by the heat during the operation of the fuel cell, and deterioration is also likely to progress. Therefore, in the fuel cell assembly of the present disclosure, the MFR of the polypropylene resin is set to 700 g / 10 min or less.
[0012] Incidentally, regarding adhesives using polypropylene-based resins, Patent Document 3 describes the use of modified polyolefins in which functional groups have been introduced into polyolefins to impart adhesive properties to bond a gas diffusion electrode and a resin frame. However, the subject of adhesion described in this document is a resin frame made of polypropylene (PP), not a rubber member. In addition, this document does not describe the melt flow rate of modified polyolefins.
[0013] Patent Document 4 describes that in an assembly including an electrode member having an MEA and a gas diffusion layer, and a gasket structure disposed on the outer periphery of the electrode member, the electrolyte membrane and the gasket structure are bonded via an adhesive layer. As a material that can be used for the adhesive layer, a hot melt adhesive such as polypropylene is described. However, the gasket structure is formed from polyethylene naphthalate (PEN), polyethylene terephthalate (PET), or polyimide (PI), and is not a rubber member. In addition, the document does not describe the melt flow rate of the adhesive. Furthermore, the document also describes a form in which a rubber sealing protrusion (lip) is disposed on the gasket structure, but the lip and the gasket structure are separate entities made of different materials, and the lip is not bonded to the electrolyte membrane or the like via an adhesive layer.
[0014] (2) In the above-mentioned (1) configuration, the adhesive member may have an antioxidant having a melting point of 160°C or more and 208°C or less. According to this configuration, the oxidative deterioration of the polypropylene-based resin can be further suppressed, and the wet heat durability of the adhesive member is further improved. In addition, in the adhesive member having the above-mentioned (1) configuration, in addition to the oxidative deterioration of the resin being less likely to progress, the intrusion of moisture and oxygen, which promote the consumption of the antioxidant, is suppressed. Therefore, the consumption rate of the antioxidant is slowed down, and the effect can be exerted for a longer period of time. Here, since the melting point of the antioxidant is 160°C or more, it does not melt at the operating temperature of the fuel cell. Furthermore, since the melting point of the antioxidant is 208°C or less, when the antioxidant is added to the polypropylene-based resin to prepare the adhesive composition, the antioxidant is easily melted and easily mixed with the polypropylene-based resin.
[0015] (3) In the above configuration (2), the content of the antioxidant may be 0.01 parts by mass or more and 10 parts by mass or less, where the mass of the polypropylene-based resin is 100 parts by mass. From the viewpoint of suppressing the oxidative deterioration of the polypropylene-based resin, it is desirable to have a large content of the antioxidant. However, since the antioxidant does not have good compatibility with the polypropylene-based resin, there is a risk of blooming if an excessive amount is contained. According to this configuration, it is possible to obtain the effect of adding the antioxidant while suppressing the blooming of the antioxidant.
[0016] (4) In the above (2) or (3), the antioxidant may be at least one selected from a phenolic compound and an amine compound, which can effectively suppress oxidative deterioration of the polypropylene resin.
[0017] (5) In any of the above configurations, the adhesive component of the adhesive member may be the polypropylene-based resin alone. This configuration can achieve high humidity and heat resistance. In addition, since no other adhesive components such as a silane coupling agent are used, the adhesive composition can be easily prepared and costs can be reduced.
[0018] (6) In any of the above configurations, the polypropylene resin may be one that is not modified with an acid. Polypropylene resins that are not modified with an acid are relatively inexpensive and available in a wide variety of products. In addition, since the polypropylene resin is not easily attached to a mold or the like, there is little risk of impairing workability in the process of preparing, applying, molding, and the like of the adhesive composition.
[0019] (7) In any of the above configurations, the adhesive member may be disposed on the periphery of the electrode member to bond the electrode member and the gasket, and the melting point of the polypropylene resin may be 130° C. or higher and 150° C. or lower. This configuration provides sufficient heat resistance to the operating temperature of the fuel cell, and reduces the heating temperature during bonding, thereby minimizing the effects on the electrolyte membrane and the like.
[0020] (8) In the above configuration (7), the electrode member may have a gas diffusion layer disposed on at least one of both surfaces in the thickness direction of the membrane electrode assembly, and the adhesive member may be impregnated into a peripheral portion of the gas diffusion layer. According to this configuration, the electrode member and the adhesive member are more firmly bonded together by impregnating a part of the adhesive member into the gas diffusion layer of the electrode member, thereby improving the sealing performance around the electrode member.
[0021] (9) In any of the configurations (1) to (6) above, the separator may have carbon powder and resin, the adhesive member may bond the separator and the gasket, and the melting point of the polypropylene resin may be 130°C or higher and 168°C or lower. The separator may be made of metal or carbon alone, or may be made by bonding carbon powder with resin. This configuration achieves sufficient heat resistance against the operating temperature of the fuel cell, and can reduce the heating temperature during bonding to suppress deformation and deterioration of the separator containing resin.
[0022] (10) In the above configuration (9), the resin contained in the separator may be one or more selected from polyphenylene sulfide resin and perfluoroalkoxyalkane resin. According to this configuration, the melting point of the resin contained in the separator is higher than the melting point of the polypropylene resin, so that deformation and deterioration of the separator due to heating during bonding is suppressed.
[0023] (11) In any of the above configurations (1) to (6), the adhesive member may be configured to bond the electrode member to the gasket and the separator to the gasket, thereby integrating the electrode member, the separator, and the gasket. According to this configuration, both the electrode member and the separator are bonded to the gasket by the adhesive member, thereby improving sealing properties and durability. In addition, the main components of the cell, including the separator, are integrated by the adhesive member. This makes it easier to handle when stacking the fuel cell assemblies, and the stacking process can be simplified. In addition, misalignment of the components during stacking is less likely to occur. This improves workability and productivity. Effect of the Invention
[0024] According to the fuel cell assembly of the present disclosure, the adhesive member and the gasket are firmly bonded, so that moisture and oxygen are less likely to penetrate, and oxidation degradation of the resin in the adhesive member is suppressed. This improves the durability of the adhesive member in a humid and hot environment, and the high sealing performance of the gasket can be maintained even when the fuel cell is operated for a long period of time. As a result, the durability of the fuel cell assembly can be improved. [Brief description of the drawings]
[0025] [Figure 1] FIG. 2 is a top view of a fuel cell assembly according to one embodiment of the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view taken along line II-II of FIG. [Diagram 3] FIG. 2 is a top view of a laminate sheet for evaluating adhesiveness produced in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] An embodiment of the fuel cell assembly of the present disclosure will be described. First, the configuration of the fuel cell assembly of this embodiment will be described. FIG. 1 shows a top view of the fuel cell assembly of this embodiment. FIG. 2 shows a cross-sectional view taken along line II-II of FIG. 1. In the orientation of the figure, the front-rear and left-right directions indicate the surface directions of each member, and the up-down direction indicates the thickness direction and stacking direction of each member. In FIG. 1, for convenience of explanation, the parts where the adhesive members are present are shown hatched. As shown in FIGS. 1 and 2, the fuel cell assembly 10 includes an electrode member 2, an upper gasket 30, a lower gasket 31, a first adhesive member 40, a second adhesive member 41, a third adhesive member 42, and a separator 50.
[0027] The electrode member 2 has a rectangular thin film shape. The electrode member 2 has an MEA 20 and a pair of an upper gas diffusion layer 21 and a lower gas diffusion layer 22 arranged on both sides in the thickness direction. The MEA 20, the upper gas diffusion layer 21, and the lower gas diffusion layer 22 have the same size (area) in the plane direction. The MEA 20 has an electrolyte membrane and a pair of electrode catalyst layers arranged on both sides in the thickness direction. The electrolyte membrane is a fully fluorinated sulfonic acid membrane, and the electrode catalyst layer has carbon particles carrying a catalyst containing platinum. The upper gas diffusion layer 21 and the lower gas diffusion layer 22 have the same configuration, and each has carbon paper. The upper gas diffusion layer 21 has an upper impregnated portion 210 impregnated with the first adhesive member 40. The upper impregnated portion 210 is arranged on the periphery of the upper gas diffusion layer 21. Similarly, the lower gas diffusion layer 22 also has a lower impregnated portion 220 impregnated with the first adhesive member 40. The lower impregnation portion 220 is disposed on the periphery of the lower gas diffusion layer 22 .
[0028] The separator 50 is a carbon plate containing carbon powder and acrylic resin, and has a rectangular thin plate shape. The electrode member 2 and the upper gasket 30 are disposed on the upper surface of the separator 50. The lower gasket 31 is disposed on the lower surface of the separator 50. In the areas of the upper and lower surfaces of the separator 50 that overlap with the electrode member 2, uneven flow paths are formed.
[0029] The upper gasket 30 has a frame shape when viewed from above, and is disposed on the outside of the electrode member 2. The upper gasket 30 is made of a cross-linked product of a rubber composition containing EPDM. The upper gasket 30 has a lip portion 300 that protrudes upward. The top of the lip portion 300 has a curved surface. When a fuel cell is constructed, the upper gasket 30 elastically contacts another fuel cell assembly that is stacked on top of it.
[0030] The lower gasket 31 is also frame-shaped, and is disposed on the lower surface of the separator 50 in a position overlapping with the upper gasket 30 when viewed from above. The lower gasket 31 is also made of a cross-linked product of a rubber composition containing EPDM, the same as the upper gasket 30. The lower gasket 31 has a lip portion 310 that protrudes downward. The top of the lip portion 310 is curved. When a fuel cell is constructed, the lower gasket 31 elastically contacts another fuel cell assembly that is stacked on top of it.
[0031] The first adhesive member 40 has a frame shape when viewed from above, and is disposed between the electrode member 2 and the upper gasket 30 in the surface direction. The first adhesive member 40 contains only a polypropylene-based resin that is not modified by acid as an adhesive component, and contains a phenol-based compound as an antioxidant. The polypropylene-based resin has an MFR of 8 g / 10 min and a melting point of 138° C. The melting point of the antioxidant is 174° C. As described above, a part of the first adhesive member 40 is impregnated into the peripheral parts of the upper gas diffusion layer 21 and the lower gas diffusion layer 22 (the upper impregnated part 210 and the lower impregnated part 220). In addition, the first adhesive member 40 is adhered to the members in contact with it, specifically, the outer peripheral end face of the MEA 20 including the electrolyte membrane and the upper gasket 30. In this way, the first adhesive member 40 adheres the electrode member 2 and the upper gasket 30.
[0032] The second adhesive member 41 has a frame shape when viewed from above, and is disposed between the upper gasket 30 and the separator 50. The components of the second adhesive member 41 are the same as those of the first adhesive member 40. The second adhesive member 41 bonds the upper gasket 30 and the separator 50. The third adhesive member 42 has a frame shape when viewed from above, and is disposed between the lower gasket 31 and the separator 50. The components of the third adhesive member 42 are also the same as those of the first adhesive member 40. The third adhesive member 42 bonds the lower gasket 31 and the separator 50. In this way, the electrode member 2, the upper gasket 30, the lower gasket 31, and the separator 50 are integrated by the first adhesive member 40, the second adhesive member 41, and the third adhesive member 42. The upper gasket 30 and the lower gasket 31 are included in the concept of the gasket constituting the fuel cell assembly of the present disclosure. The first adhesive member 40, the second adhesive member 41, and the third adhesive member 42 are included in the concept of adhesive members that make up the fuel cell assembly of the present disclosure.
[0033] Next, a method for manufacturing the fuel cell assembly of this embodiment will be described The method for manufacturing the fuel cell assembly of this embodiment includes a gasket molding step, a bonding step of the gasket and the separator, and a step of integrating the electrode members.
[0034] (1) Gasket molding process In this process, an EPDM-containing rubber composition is injection molded to mold upper gasket 30 and lower gasket 31 separately.
[0035] (2) Bonding process between gasket and separator In this process, first, the lower gasket 31 is placed in a press machine, and the adhesive composition, which is the material of the third adhesive member 42, is applied to a predetermined position on the upper surface of the lower gasket 31 using a dispenser. The adhesive composition is heated to a temperature of 140°C or higher in advance so as to have a desired fluidity (hereinafter, the same applies to the case where the adhesive composition of the second adhesive member 41 and the first adhesive member 40 is applied using a dispenser). Next, the separator 50 is laminated, and the adhesive composition made of the material of the second adhesive member 41 is applied to a predetermined position on the upper surface of the separator 50 using a dispenser, and then the upper gasket 30 is laminated. Then, the laminated portion of the upper gasket 30 and the lower gasket 31 is pressed with a press plate heated to 140°C. Thereafter, the adhesive composition is hardened by natural cooling, and a gasket-attached separator is manufactured in which the upper gasket 30, the separator 50, and the lower gasket 31 are integrated by the second adhesive member 41 and the third adhesive member 42.
[0036] (3) Electrode component integration process In this process, first, the manufactured gasketed separator is placed in a press machine, and the electrode member 2 is placed inside the upper gasket 30. Next, an adhesive composition made of the material of the first adhesive member 40 is applied to the gap between the electrode member 2 and the upper gasket 30 using a dispenser. Then, the laminate is pressed with a press plate heated to 140°C. This causes the adhesive composition to permeate the peripheral portions of the upper gas diffusion layer 21 and the lower gas diffusion layer 22 of the electrode member 2. The adhesive composition is then cured by natural cooling, and a fuel cell assembly 10 is manufactured in which the gasketed separator and the electrode member 2 are integrated by the first adhesive member 40.
[0037] Next, the effects of the fuel cell assembly of this embodiment and the manufacturing method thereof will be described. The adhesive members (first adhesive member 40, second adhesive member 41, and third adhesive member 42) of the fuel cell assembly 10 of this embodiment contain polypropylene resin with MFR of 8 g / 10 minutes as an adhesive component. In addition, each adhesive member contains an antioxidant. On the other hand, the gaskets (upper gasket 30 and lower gasket 31) are made of EPDM. Therefore, the adhesive properties between each adhesive member and the gasket are good, and the adhesive members have high wet heat durability. In addition, since the MFR of the polypropylene resin is relatively large, the adhesive composition can be applied using a dispenser, and productivity can be improved. In addition, the adhesive composition can be impregnated into the upper gas diffusion layer 21 and the lower gas diffusion layer 22 of the electrode member 2 to increase the adhesive properties. In addition, the melting point of the polypropylene resin is 138°C, and the hot press in the bonding process between the gasket and the separator is performed at 140°C, so that the separator 50 containing the acrylic resin is unlikely to deform when heated. Similarly, because the hot pressing in the electrode member integration process is performed at 140°C, there is little risk of the electrolyte membrane deteriorating when heated. In the fuel cell assembly 10, both the electrode member 2 and the separator 50 are bonded to the gasket with an adhesive member and integrated together. This improves sealing performance and durability, improves the handleability of the fuel cell assembly 10, and makes it less likely for members to become misaligned.
[0038] The above describes one embodiment of the fuel cell assembly of the present disclosure, however, the fuel cell assembly of the present disclosure is not limited to the above-described form, and can be embodied in various forms incorporating modifications and improvements that can be made by those skilled in the art, without departing from the gist of the present disclosure.
[0039] The fuel cell assembly of the present disclosure may have an electrode member, a gasket, and an adhesive member as essential components. In the fuel cell assembly of the present disclosure, other components may be present in addition to these essential components, and the types of components are not limited. The components adhered to the gasket by the adhesive member may be either one or both of the electrode member and the separator. For example, a gasketed electrode member in which the electrode member and the gasket are integrated by the adhesive member may be laminated on a separator to form a fuel cell assembly. Also, a gasketed separator in which the separator and the gasket are integrated by the adhesive member may be combined with an electrode member to form a fuel cell assembly.
[0040] <Electrode materials> Among the components of the fuel cell assembly of the present disclosure, the electrode member has an MEA. The MEA has an electrolyte membrane and a pair of electrode catalyst layers arranged on both sides of the electrolyte membrane. The electrolyte membrane may be a proton-conductive ion exchange membrane used in fuel cells. The electrode catalyst layer may be composed of a conductive carrier carrying a catalyst such as platinum or a platinum alloy. The electrode catalyst layer does not necessarily have to be formed on the entire surface of the electrolyte membrane. The electrode catalyst layer may be appropriately formed on the surface of the electrolyte membrane according to the power generation region in the MEA. The electrode member desirably has a gas diffusion layer as a member responsible for diffusing gas supplied to the MEA, moisturizing the electrolyte membrane, discharging water generated during power generation, and collecting electrons. The gas diffusion layer may be a carbon porous body such as carbon paper or carbon cloth, or a metal porous body such as a metal mesh.
[0041] The gas diffusion layer may be disposed on one or both sides in the thickness direction of the MEA. The gas diffusion layer may be a single layer or two or more layers. When the gas diffusion layer is disposed on both sides in the thickness direction of the MEA, the thickness of the gas diffusion layer and the size in the surface direction (area) may be the same or different between the one side and the other side in the thickness direction. For example, when the area of the gas diffusion layer disposed on one side is smaller than the area of the gas diffusion layer disposed on the other side, a part of the MEA is exposed on the gas diffusion layer side with the smaller area. In this embodiment, when the electrode member and the gasket are bonded with an adhesive member, it is desirable to bond the adhesive member to the exposed part of the MEA from the viewpoint of protecting the electrolyte membrane. Also, when the area of the MEA is larger than the area of the gas diffusion layer, a part of the MEA is exposed. Even in this embodiment, it is desirable to bond the adhesive member to the exposed part of the MEA from the viewpoint of protecting the electrolyte membrane.
[0042] <Gasket> The gasket is not particularly limited in its arrangement or shape as long as it is disposed on the outer side of the electrode member in the planar direction. For example, in addition to being disposed around the electrode member, the gasket may be disposed between separators, or disposed so as to surround a predetermined portion such as a manifold hole opened in a separator. The gasket may be manufactured by subjecting a rubber composition having a solid rubber to injection molding, press molding, or the like. The solid rubber is one or more selected from ethylene-propylene rubber, ethylene-propylene-diene rubber, and ethylene-butene-diene rubber. The rubber composition may contain a crosslinking agent, a crosslinking aid, a plasticizer, a reinforcing agent, an antioxidant, a processing aid, and the like in addition to the rubber component. As the crosslinking agent, it is preferable to use an organic peroxide because it does not contain a volatile component such as sulfur. In the above embodiment, a lip portion is disposed on the gasket from the viewpoint of improving the sealing property when the fuel cell assemblies are stacked. The shape and thickness of the gasket, including the presence or absence of a lip portion, may be appropriately determined.
[0043] <separator> Examples of the separator material include stainless steel, titanium, copper, magnesium, aluminum, carbon, graphite, ceramics, and conductive resin (thermoplastic resin or thermosetting resin having carbon, graphite, polyacrylonitrile carbon fiber, etc.). Among separators made of conductive resin, for example, a carbon plate formed by binding carbon powder with a resin is often preferable because it is low cost compared to a separator made of metal. The resin to be the binder may be appropriately selected in consideration of the characteristics required for the separator and the melting temperature of the adhesive composition. Examples include polyethylene resin, polypropylene resin, phenol resin, acrylic resin, polyphenylene sulfide resin, and perfluoroalkoxyalkane resin. Among them, polyphenylene sulfide resin and perfluoroalkoxyalkane resin have a high melting point, so that the separator is less likely to deform or deteriorate due to heating during adhesion.
[0044] Furthermore, a carbon thin film such as a diamond-like carbon film (DLC film) or a graphite film may be formed on the surface of the main body made of these materials by a process such as physical vapor deposition (PVD) or chemical vapor deposition (CVD). From the viewpoint of facilitating the attachment of the adhesive composition and enhancing adhesion, a surface treatment such as forming projections and recesses may be performed. The configuration of the separator, including the formed flow paths, manifold holes, etc., is not limited, and the shape, thickness, etc. may be appropriately determined.
[0045] <Adhesive materials> The adhesive member has a polypropylene resin with an MFR of 7 g / 10 min to 700 g / 10 min. From the viewpoints of reducing the viscosity of the adhesive composition to increase productivity when applying the adhesive composition using a dispenser or the like, making it easier to impregnate the peripheral portion of the gas diffusion layer, and making it easier to adhere to uneven surfaces such as separators, it is desirable for the MFR to be 8 g / 10 min or more, and even 360 g / 10 min or more. On the other hand, in consideration of deformation and deterioration in a humid and hot environment, it is desirable for the MFR to be 600 g / 10 min or less.
[0046] From the viewpoint of the adhesiveness and wet heat durability of the adhesive member, the polypropylene-based resin alone is sufficient as the adhesive component. However, the adhesive member may contain other adhesive components within a range that does not impair the effect of the polypropylene-based resin. The structure of the polypropylene-based resin is not particularly limited, such as a homopolymer, a random copolymer, a block copolymer, etc. The polypropylene-based resin may be modified with or without acid. That is, the polypropylene-based resin may be modified with an acid, an acid anhydride, an acid ester, a metallocene, or the like, or may not be modified. The modification with acid may be performed by grafting an acid component to the polypropylene-based resin, copolymerizing it, or a combination of these. Polypropylene-based resins that are not modified with acid are relatively inexpensive and have a wide variety of products. In addition, since it is difficult to adhere to a mold, etc., using a polypropylene-based resin that is not modified with acid has the advantage that there is little risk of impairing the workability in the process of preparing, applying, molding, etc. of the adhesive composition.
[0047] Considering the operating temperature of the fuel cell, the melting point of the polypropylene-based resin is desirably 130°C or higher. On the other hand, when the adhesive member is bonded to the electrode member, the melting point of the polypropylene-based resin is desirably 150°C or lower, taking into consideration the heat resistance temperature of the electrolyte membrane. The adhesive member may be bonded to the electrode member by impregnating the gas diffusion layer, by bonding to the MEA, or by both. When the adhesive member is bonded to the separator, and the separator contains a component such as a resin that has a relatively low heat resistance, the melting point of the polypropylene-based resin is desirably 168°C or lower in order to suppress deformation or deterioration of the separator.
[0048] The adhesive member may contain a component other than the adhesive component. For example, when an antioxidant is contained, the oxidative deterioration of the polypropylene resin is suppressed, and the wet heat durability of the adhesive member is further improved. The melting point of the antioxidant is desirably 160°C or higher, taking into consideration the operating temperature of the fuel cell. In addition, from the viewpoint of making it easier to prepare the adhesive composition, it is desirably 208°C or lower. Examples of the antioxidant include phenolic compounds, amine compounds, imidazole compounds, and phosphoric acid compounds. Among them, it is desirably to use one or more selected from phenolic compounds and amine compounds because they have a high effect of suppressing the oxidative deterioration of the polypropylene resin. From the viewpoint of suppressing the oxidative deterioration of the polypropylene resin, it is preferable to set the content of the antioxidant to 0.01 parts by mass or more when the mass of the polypropylene resin is 100 parts by mass. It is more preferable to set the content to 0.1 parts by mass or more. On the other hand, since the antioxidant does not have good compatibility with the polypropylene resin, if it is contained in an excessive amount, there is a risk of blooming. Therefore, the content of the antioxidant is preferably 10 parts by mass or less, more preferably 2 parts by mass or less, and even more preferably 0.2 parts by mass or less, based on 100 parts by mass of the polypropylene resin.
[0049] <Method of Manufacturing Fuel Cell Assembly> The fuel cell assembly of the present disclosure is manufactured by forming a gasket in advance, and bonding the formed gasket and electrode members, etc., by utilizing the melting and hardening of the polypropylene-based resin in the adhesive composition. The adhesive composition can be supplied by applying the molten gasket with a brush, a coating machine such as a dispenser, a spray, etc., using a mold, or by arranging an adhesive sheet in which the adhesive composition is previously formed into a sheet shape. When the adhesive composition is melted and hardened, a hot press machine or the like may be used. Alternatively, when the adhesive composition is injected into a mold and hardened, an injection molding machine or the like may be used. When the adhesive composition is melted and bonded, it is not necessarily required to apply pressure, but when the adhesive composition is applied in a molten state, it is easy to impregnate, for example, a gas diffusion layer. The heating temperature for melting the adhesive composition may be appropriately determined in consideration of the melting point of the polypropylene-based resin, the heat resistance of the member, etc. The pressure when applying pressure may be appropriately determined in consideration of the adhesiveness, the suppression of destruction of the member, etc. EXAMPLES
[0050] Next, the present disclosure will be described in more detail with reference to examples. Samples were produced by bonding the adhesive member to the member to be bonded, and the adhesiveness and wet heat durability of the samples were evaluated. The members to be bonded were a rubber sheet corresponding to a gasket, a metal plate corresponding to a separator, and a carbon plate.
[0051] (1) When the member to be bonded is a rubber sheet: Examples 1 to 4, Comparative Examples 1 to 3 <Sample Production> First, a rubber sheet was manufactured as follows. 100 parts by mass of EPDM (Sumitomo Chemical Co., Ltd.'s "Esprene (registered trademark) 505") as a rubber component, 6 parts by mass of dialkyl peroxide (NOF Corp.'s "Perhexa (registered trademark) 25B-40") as a crosslinking agent, 20 parts by mass of paraffin-based process oil (Idemitsu Kosan Co., Ltd.'s "Diana (registered trademark) Process Oil PW380") as a plasticizer, and 50 parts by mass of carbon black (Tokai Carbon Co., Ltd.'s "Seast (registered trademark) S") as a reinforcing agent were kneaded using a Banbury mixer and an open roll to prepare a rubber composition. The prepared rubber composition was crosslinked by holding it at 185°C for 10 minutes while pressing it using a press machine, to manufacture a rubber sheet with a thickness of 2 mm. The manufactured rubber sheet was cut into a rectangular shape with a length (long side) of 100 mm and a width (short side) of 40 mm, and used for manufacturing samples.
[0052] Next, adhesive sheets 0.6 mm thick were produced from various adhesive compositions shown in Table 1 below, and these were cut into rectangular shapes of 100 mm length and 40 mm width for use in producing samples. The raw materials used in producing the adhesive compositions are as follows: [Polypropylene resin] PP-A: "Admer (registered trademark) QE060" manufactured by Mitsui Chemicals, Inc., MFR 7 g / 10 min, melting point 140°C. PP-B: "Hardlen (registered trademark) PMA-F2" manufactured by Toyobo Co., Ltd., MFR 720 g / 10 min, melting point 120°C. PP-C: "Noblen (registered trademark) AD571" manufactured by Sumitomo Chemical Co., Ltd., MFR 0.6 g / 10 min, melting point 165°C. PP-D: "Noblen (registered trademark) W531D" manufactured by Sumitomo Chemical Co., Ltd., MFR 8 g / 10 min, melting point 138°C. PP-E: "S23B" manufactured by Prime Polymer Co., Ltd., MFR 360g / 10min, melting point 133℃. [Polyethylene resin] "Novatec (registered trademark) HD HF560" manufactured by Japan Polyethylene Co., Ltd., MFR 7g / 10min, melting point 134°C. [Antioxidants] Phenol compound, "ANTAGE (registered trademark) HP-200" manufactured by Kawaguchi Chemical Industry Co., Ltd., melting point 174°C.
[0053] A release paper was placed on the rubber sheet, and the adhesive sheet was laminated with a 10 mm shift in the horizontal direction, and the rubber sheet side was placed down on an iron plate heated to 194 ° C. Then, the adhesive sheet side was pressed with a press plate heated to 140 ° C for 5 minutes. Two release papers were placed side by side at the part where the rubber sheet and the adhesive sheet overlap, with a gap of 3 mm in the horizontal direction. As a result, the adhesive sheet melts when pressed by the press plate, and the molten material passes through the gap in the release paper and reaches the rubber sheet. After this, the sheets were naturally cooled at room temperature (20 ° C ± 5 ° C), the molten material hardened, and both sheets were bonded. Then, the release paper was removed, and a laminated sheet was obtained in which the rubber sheet and the adhesive sheet were bonded at a 3 mm wide adhesive part extending in the vertical direction. Figure 3 shows a top view of the obtained laminated sheet. In Figure 3, for convenience of explanation, the rubber sheet 81 overlapping the adhesive sheet 82 is shown in a see-through manner. 3, the adhesive portion 83 between the rubber sheet 81 and the adhesive sheet 82 is shown hatched. As shown by the dotted line in FIG. 3, the laminated sheet 80 was cut along the short side to a width of 5 mm to prepare a rectangular sample 84, which was subjected to a tensile peel test to evaluate the adhesiveness.
[0054] <Sample evaluation method> The adhesion of the samples was evaluated by the peel force measured in the following tensile peel test. In the tensile peel test, a rectangular sample was pulled in the longitudinal direction (horizontal direction in Figure 3) at a speed of 10 mm / sec, and the stress at which the two sheets peeled off was measured. If the stress at the time of peeling was 0.4 MPa or more, the adhesion was evaluated as good (indicated by a circle in Table 1 below), and if it was less than 0.4 MPa, the adhesion was evaluated as poor (indicated by a cross in the same table).
[0055] The tensile peel test was carried out on three types of samples: "initial", "500 hours in a humid heat environment", and "1500 hours in a humid heat environment". The "initial" sample was a sample that was left at room temperature after being manufactured as a strip-shaped sample. The "500 hours in a humid heat environment" and "1500 hours in a humid heat environment" samples were manufactured by placing the samples in a pressure-resistant container, holding them in an atmosphere filled with water vapor at 120°C (humid heat environment) for 500 or 1500 hours, and then removing them and naturally cooling them at room temperature. For the samples held in a humid heat environment, the appearance of the adhesive member (adhesive sheet) was visually observed for embrittlement. The results of the samples held in a humid heat environment are an index for evaluating the humid heat durability of the adhesive member. The evaluation results of the adhesion will be described later.
[0056] (2) When the members to be bonded are a rubber sheet and a carbon plate: Examples 5 and 6 <Sample Production> First, a carbon separator (manufactured by FJ Composite Co., Ltd., thickness 0.3 mm) made of carbon powder and polyphenylene sulfide (PPS) resin was cut into a 50 mm square to form a first carbon plate. Separately, a carbon separator (manufactured by FJ Composite Co., Ltd., thickness 0.3 mm) made of carbon powder and perfluoroalkoxyalkane (PFA) resin was cut into a 50 mm square to form a second carbon plate. Next, a rubber sheet having a thickness of 1.5 mm was manufactured in the same manner as in the manufacture of the sample (1) described above, and this was cut into a strip having a width of 2 mm and a length of 60 mm. Next, an adhesive sheet having a thickness of 80 μm was manufactured from an adhesive composition having a polypropylene resin (PP-A: "Admer (registered trademark) QE060" manufactured by Mitsui Chemicals, Inc., MFR 7 g / 10 min, melting point 140 ° C.), and this was cut into a strip having a width of 2 mm and a length of 40 mm. Then, a strip-shaped adhesive sheet and a strip-shaped rubber sheet were laminated in this order on the first and second carbon plates, with one of the short sides aligned. The 20 mm length of the rubber sheet that did not overlap the adhesive sheet served as a gripping portion when conducting a tensile peel test. The laminated portion was then pressed from the rubber sheet side with a heated press plate for one minute. The temperature of the press plate was 170°C, and the surface pressure was 2 MPa. After this, the samples were naturally cooled at room temperature, and two types of laminate samples in which the carbon plate and the rubber sheet were bonded with the adhesive sheet (adhesive member) were obtained.
[0057] <Sample evaluation method> The laminate sample was set in a universal material testing machine (Strograph, manufactured by Toyo Seiki Seisakusho Co., Ltd.), and the gripped portion of the rubber sheet was pulled at a speed of 10 mm / sec to measure the stress at which the rubber sheet peeled off. If the stress at the time of peeling was 0.4 MPa or more, it was evaluated as good adhesion (indicated by a circle in Table 1 below), and if it was less than 0.4 MPa, it was evaluated as poor adhesion (indicated by a cross in the same table). This tensile peel test was carried out on three types of laminate samples, "initial", "after 500 hours in a humid heat environment", and "after 1500 hours in a humid heat environment", in the same manner as in the evaluation method of the samples in (1) above. The evaluation results of adhesion will be described later.
[0058] (3) When the members to be bonded are a rubber sheet and a metal plate: Example 7 <Sample Production> A laminate sample in which a metal plate and a rubber sheet were bonded with an adhesive sheet (adhesive member) was produced in the same manner as in the production of sample (2) described above, except that the carbon separator was changed to a stainless steel (SUS304) plate (manufactured by JX Metals Corporation, thickness 0.1 mm) to form a 50 mm square metal plate.
[0059] <Sample evaluation method> In the same manner as in the evaluation method for the samples described above in (2), tensile peel tests were performed on the three types of laminate samples: "initial", "after 500 hours in a humid and hot environment", and "after 1,500 hours in a humid and hot environment", to evaluate their adhesion.
[0060] (4) Evaluation results Table 1 shows the components of the adhesive composition (adhesive member) and the evaluation results of the adhesiveness. In Table 1, the overall evaluation of the adhesiveness is shown as "A" when all three types of samples have good adhesiveness, "B" when only the sample after 1500 hours in a humid heat environment has poor adhesiveness, and "C" otherwise. In this example, if the overall evaluation was "A" or "B", it was evaluated as excellent adhesiveness and humid heat durability. [Table 1]
[0061] As shown in Table 1, in the samples of Examples 1 to 7 using a polypropylene resin with an MFR of 7 g / 10 min to 700 g / 10 min as the adhesive member, the overall evaluation was A except for Example 4, and it was confirmed that the adhesive member has excellent adhesion and wet heat durability regardless of whether the member to be adhered is a rubber sheet, a metal plate, or a carbon plate. In the sample of Example 4, the adhesive member does not contain an antioxidant. Therefore, the adhesiveness after 1500 hours in a wet heat environment decreased, and the overall evaluation was B. In addition, in the samples of Examples 1 to 7, no embrittlement was observed in the appearance of the adhesive member even after exposure to a wet heat environment.
[0062] On the other hand, the sample of Comparative Example 1, which used a polypropylene-based resin with a low MFR of 0.6 g / 10 min, had poor initial adhesion. The sample of Comparative Example 2, which used a polypropylene-based resin with a high MFR of 720 g / 10 min, had good initial adhesion, but the resin had a low melting point and was easily deformed in a humid and hot environment, so the adhesion decreased when exposed to a humid and hot environment. In addition, the sample of Comparative Example 2 showed embrittlement of the adhesive member after exposure to a humid and hot environment. In the sample of Comparative Example 3, a polyethylene-based resin was used as the adhesive member. This resulted in poor initial adhesion. [Explanation of symbols]
[0063] 10: fuel cell assembly, 2: electrode member, 20: MEA, 21: upper gas diffusion layer, 22: lower gas diffusion layer, 210: upper impregnated portion, 220: lower impregnated portion, 30: upper gasket, 300: lip portion, 31: lower gasket, 310: lip portion, 40: first adhesive member, 41: second adhesive member, 42: third adhesive member, 50: separator, 80: laminated sheet, 81: rubber sheet, 82: adhesive sheet, 83: adhesive portion, 84: sample.
Claims
1. an electrode member having a membrane electrode assembly having an electrolyte membrane and an electrode catalyst layer; a gasket that is disposed on an outer side of the electrode member in a planar direction, the gasket being made of a rubber composition having a solid rubber, the gasket having a planar direction that intersects with a thickness direction of the electrode member; a separator laminated on the electrode member and the gasket; an adhesive member having a polypropylene-based resin and bonding at least one of the electrode member and the separator to the gasket; Equipped with the solid rubber is at least one selected from the group consisting of ethylene-propylene rubber, ethylene-propylene-diene rubber, and ethylene-butene-diene rubber; The polypropylene resin has a melt flow rate (MFR) measured at a temperature of 230° C. under a load of 2.16 kg of 7 g / 10 min or more and 700 g / 10 min or less.
2. 2. The fuel cell assembly according to claim 1, wherein the adhesive member contains an antioxidant having a melting point of 160°C or higher and 208°C or lower.
3. 3. The fuel cell assembly according to claim 2, wherein a content of the antioxidant is from 0.01 parts by mass to 10 parts by mass, both inclusive, relative to 100 parts by mass of the polypropylene resin.
4. 3. The fuel cell assembly according to claim 2, wherein the antioxidant is at least one selected from the group consisting of phenol-based compounds and amine-based compounds.
5. 2. The fuel cell assembly in accordance with claim 1, wherein the adhesive component of the adhesive member is only the polypropylene-based resin.
6. 2. The fuel cell assembly according to claim 1, wherein the polypropylene resin is not modified by an acid.
7. the adhesive member is disposed on a peripheral portion of the electrode member and bonds the electrode member and the gasket; 2. The fuel cell assembly according to claim 1, wherein the melting point of the polypropylene resin is 130°C or higher and 150°C or lower.
8. the electrode member has a gas diffusion layer disposed on at least one of both surfaces in a thickness direction of the membrane electrode assembly, The fuel cell assembly according to claim 7 , wherein the adhesive member is impregnated into the peripheral portion of the gas diffusion layer.
9. The separator includes carbon powder and a resin, the adhesive member bonds the separator and the gasket together, 2. The fuel cell assembly according to claim 1, wherein the melting point of the polypropylene resin is 130°C or higher and 168°C or lower.
10. 10. The fuel cell assembly in accordance with claim 9, wherein the resin contained in the separator is at least one selected from the group consisting of polyphenylene sulfide resin and perfluoroalkoxyalkane resin.
11. 2 . The fuel cell assembly according to claim 1 , wherein the adhesive member bonds the electrode member to the gasket and bonds the separator to the gasket, thereby integrating the electrode member, the separator, and the gasket.
Citation Information
Patent Citations
Electrolyte membrane-electrode assembly
JP2007066766A
Method of manufacturing battery electrode
JP2014022131A
Manufacturing method of fuel cell seal body, and rubber gasket for fuel cell used therein
JP2017183198A
Composite member and method for producing the same
JP2023034863A